2020
DOI: 10.1111/clr.13578
|View full text |Cite
|
Sign up to set email alerts
|

Guidance means accuracy: A randomized clinical trial on freehand versus guided dental implantation

Abstract: Objectives: A randomized clinical trial was conducted to compare all three known static guided surgery protocols (pilot, partial, and full) with each other and with freehand surgery in terms of accuracy, under the same conditions. Material and Methods:A total of 207 implants of the same brand and type were placed in 101 partially edentulous volunteers in need of implantation in the mandible or maxilla or both. All cases were digitally planned, and the comparison of the planned and actual implant positions was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
87
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(102 citation statements)
references
References 25 publications
(57 reference statements)
3
87
0
4
Order By: Relevance
“…Clinically, a fully guided surgery protocol might be recommended to minimize the deviation. Two RCT studies comparing different guided surgery protocol also reported that fully guided surgery protocol showed better results in comparison with the cases using a surgical guide plate only at pilot drill [29,30].…”
Section: Discussionmentioning
confidence: 96%
“…Clinically, a fully guided surgery protocol might be recommended to minimize the deviation. Two RCT studies comparing different guided surgery protocol also reported that fully guided surgery protocol showed better results in comparison with the cases using a surgical guide plate only at pilot drill [29,30].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, the drilling procedure executed in post‐extraction sockets augmented the distance from sleeve to the bone, and this fact has been also related with inaccuracy of the guided surgery 26 . Despite these factor, the degree of deviation showed in this study was within the range found by other clinical studies, 19,23,25 and it is likely that factors such as the use of tooth ‐supported guides guide, the installation of the implants in the anterior region and the method of making the guide by association of tomography with oral scanning may have reduced the effects of alteration in the accuracy of the guided surgery 21 by the factors mentioned above.…”
Section: Discussionmentioning
confidence: 48%
“…One of the parameters that may influenced the accuracy of the guided surgery is the degree of the perforation that the clinician can performed using the guides 19 . The surgery is considered fully guided whenever a 3D printed surgical stent is used to prepare the implant site with proper surgical drills and the implant is installed with the stent in position 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the main challenge for the prosthetic treatment team (dentist, dental technician) in the implementation of a fully digital All-on-X workflow is to transfer the final implant position to the definitive restoration. The deviations between the virtually planned and the real implant position must be balanced out even with guided implantation [ 18 25 ].…”
Section: Introductionmentioning
confidence: 99%